Do Assistive Technologies Moderate the Effect of Transformational Leadership on the Workplace Well-Being of Disabled Employees? - Wided Ragmoun; Abdulaziz Alfalih (IEEE Access)
Exploring the transformation leadership dimensions and workplace well-being from the perspective of disabled employees is an important research problem in recent times. However, the association between transformational leadership dimensions and the workplace well-being of disabled employees has not received due attention in the available empirical literature. In this state, the current paper investigates the association between transformational leadership dimensions and workplace well-being by focusing on disabled employees in organizations. In addition, it aims to examine the moderating effect of assistive technologies between these variables. To this end, this research adopted a quantitative approach based on the SPSS macro-PROCESS to interpret data collected from 319 disabled employees using a survey. The findings confirmed the limited positive relationships between transformational leadership and the well-being of disabled employees at work. This impact is still significant for three components of well-being at work, including job satisfaction in the first level, perceived discrimination, and the need for recovery. Further, this research supports that the moderating effect of assistive technology exists and is still positive for satisfaction with the use of assistive technology and the frequency of its use. Findings offer a new use of transformational leadership theory in disability management through the lenses of The Technology Acceptance Model.